2012
DOI: 10.1038/mp.2012.113
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide association study of post-traumatic stress disorder identifies the retinoid-related orphan receptor alpha (RORA) gene as a significant risk locus

Abstract: We describe the results of the first genome-wide association study of PTSD performed using trauma-exposed white non-Hispanic participants from a cohort of veterans and their intimate partners (295 cases and 196 controls). Several SNPs yielded evidence of association. One SNP (rs8042149), located in the retinoid-related orphan receptor alpha gene (RORA), reached genome-wide significance. Nominally significant associations were observed for other RORA SNPs in two African American replication samples—one from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
197
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 212 publications
(206 citation statements)
references
References 44 publications
5
197
4
Order By: Relevance
“…This finding was supported by a smaller, independent VA cohort including 491 EA veterans and their intimate partners with 313 lifetime-PTSD cases (Logue et al, 2013a). PRTFDC1 is a ∼100 kb long gene located on chromosome 10p12.…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…This finding was supported by a smaller, independent VA cohort including 491 EA veterans and their intimate partners with 313 lifetime-PTSD cases (Logue et al, 2013a). PRTFDC1 is a ∼100 kb long gene located on chromosome 10p12.…”
Section: Discussionmentioning
confidence: 70%
“…In regards to our inability to replicate previous findings from GWASs, which met the stringent genome-wide significant thresholds, power calculations indicated that MRS was sufficiently powered for a replication of rs8042149 in RORA (Logue et al, 2013a) for EA's (OR 2.1 in original study and 1.22 in MRS; data not shown). However, the association of rs6812849 in TLL1 (Xie et al, 2013) was originally detected in a larger study, and rs10170218 in LINC01090 (Guffanti et al, 2013) was originally found in an all-female AA cohort, which was also larger than the all-male MRS AA cohort, and MRS findings for these genes remain inconclusive.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations